Economic value determination as a strategy for building resilient communities in the Niger Delta region - Akujuru, Victor A.; Ruddock, Les (International Journal of Strategic Property Management, 2016)
In a novel approach to disaster resilience that embodies a multidisciplinary problem solving process in determining the value of damaged property, a framework has been developed for determining the economic value of damages to property due to contamination from human-caused oil spill disaster in the Niger Delta. The framework will result in a reduction of the recovery process of affected communities following an oil spill as they know in advance what will be done and result in standardisation of the valuation process. it will enable the polluter to know the cost of their malfeasance and provide the property owners with the economic value of their polluted property to enable them to continue their livelihood. Professional valuers and property owners are very dissatisfied with the current practice without a standard framework and oil company operators hardly realise the economic cost of disasters imposed on the communities. Reviewing the theory and practice of economic value and ecosystem valuation, a mixed-methodology was employed using questionnaires and expert interviews to ascertain how contaminated wetland property is valued, the professionals involved and their respective roles. The proposed framework will provide a systematic process leading to the determination of the economic value of damages due to contamination of wetlands property.